Microdosimetry for hadron therapy: A state of the art of detection technology - Parisi, Gabriele; Romano, Francesco; Schettino, Giuseppe (Frontiers in Physics, 2022)
The interest in hadron therapy is growing fast thanks to the latest technological advances in accelerator and delivery technologies, to the development of more and more efficient and comprehensive treatment planning tools and to its increasing clinical adoption proving its efficacy. To exploit at best its advantages with respect of conventional radiotherapy, a precise and reliable beam qulity assessment and an accurate and effective inclusion of the different biological effectiveness of different radiation qualities are fundamental. In clinical practice, quality assurance (QA) is currently carried out by means of conventional dosimetry, while the biological effectiveness is taken into account considering the Relative Biological Effectiveness (RBE), which is currently considered a constant value for protons or estimated as a function of the absorbed dose in case of carbon ions. In this framework, microdosimtery could bring a significance improvement to both QA and RBE estimation. By measuring the energy deposited by the radiation into cellular or sub-cellular volumes, microdosimetry could provide a unique characterisation of the beam quality on one hand, and a direct link to radiobiology on the other. Different detectors have been developed for microdosimetry and applied to hadron therapy beams, from the more conventional tissue equivalent proportional counter (TEPC), gas electrons multiplier (GEM), silicon-based and diamond-based solid-state detectors, to ΔE-E telescope detectors, hybrid microdosimeters and a micro-bolometer based on SQUID technology. However, because of their different advantages and drawbacks, a standard device and an accredited experimental methodology have not been unequivocally identified yet. The establishment of accepted microdosimetry standard protocols and code of practice is needed before the technique could be employed in clinical practice. Hoping to help creating a solid ground on which future research, development and collaborations could be planned and inspired, a comprehensive state of the art of the detector technologies developed for microdosimetry is presented in this review, discussing their use in clinical hadron therapy conditions and considering their advantages and drawbacks.